A passion for freedom : the story of Kisanin Jaggi Devi - Mehrotra, Deepti Priya (New Delhi : Indira Gandhi National Centre for the Arts, 2007)
On the life and works of Jaggi Devi, 1917-1989, freedom fighter from Uttar Pradesh, India.
Keywords: Devi, Kisanin Jaggi, -- 1917-1989.; Philosophers -- Biography -- India; India -- Philosophy -- History